P504VT ablation outcomes and predictors in a UK population- validating existing predictors and novel markers. (18th June 2020) - Ahluwalia, N; Graham, A; Orini, M; Williams, S; Ahsan, S; Khan, F; Ezzat, V; Sporton, S; Earley, M; Chow, A; Lambiase, P; Dhinoja, M
Abstract: Background: Radiofrequency catheter ablation (CA) can reduce ventricular tachycardia (VT) burden and registry data suggests an improvement in mortality. However, there is significant heterogeneity in patient morbidity and VT phenotype. A risk prediction model derived from observational data has suggested pre-procedural left ventricular (LV) function, age and underlying ischaemic cardiomyopathy are associated with greater post-procedural mortality. Validation of proposed factors in clinical practice is required to facilitate comprehensive pre-procedural risk stratification and inform decision making. Purpose: To determine whether proposed pre-procedural predictors of mortality after VTCA are valid in a UK population and explore any association with other predictors. Method: Patients undergoing VTCA at a tertiary electrophysiology centre between 06/07/16 and 31/07/19 were included. Pre-specified characteristics and mortality follow-up data were analysed from electronic health records. Cox regression analysis was undertaken to determine association with mortality. Results: 161 patients with mean age of 63 ±15.9 years underwent VTCA of whom 133 (83%) were male. During the follow-up period (16 months, 13-24; median, 1st-3rd quartile) 16 patients died. No deaths occured in the 27 (16%) patients with structurally normal hearts. Chronic kidney disease (CKD) stage III-IV (HR 14.73 [4.9-44.4]), LV ejection fraction <35% (HR 7.13 [1.59-31.88]), underlying ischaemic cardiomyopathy (HR 6.17 [1.37-27.85]), LV internal diameter (LVID) (1.08 [1.02-1.15]) and age (HR 1.08 [1.02-1.14]) were associated with significantly greater mortality risk (Table 1) (Figure 1). Conclusion: Proposed risk stratifying factors are validated in our UK centre's experience. Additionally, CKD and baseline LVID appear to be associated with mortality in our population and warrant further study.